The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7150/ijbs.24626
|View full text |Cite
|
Sign up to set email alerts
|

GeneFuse: detection and visualization of target gene fusions from DNA sequencing data

Abstract: In recent years, gene fusion detection for cancer treatment has become increasingly important since more therapeutic agents have been developed to suppress fusion kinases. Although a number of tools have been developed to detect gene fusions from DNA sequencing data, most of them are not sensitive enough for processing the data from the samples with low tumor DNA composition, like cell-free tumor DNA. In this paper, we will introduce GeneFuse, a tool to detect and visualize gene fusions with high sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 22 publications
(14 reference statements)
0
43
0
Order By: Relevance
“…N base) is ignored. This k-mer representation has been used widely in our previous works, such as GeneFuse [ 28 ]. A progressive method for k-mer calculation is applied to accelerate k-mer generation.…”
Section: Methodsmentioning
confidence: 99%
“…N base) is ignored. This k-mer representation has been used widely in our previous works, such as GeneFuse [ 28 ]. A progressive method for k-mer calculation is applied to accelerate k-mer generation.…”
Section: Methodsmentioning
confidence: 99%
“…N base) is ignored. This k-mer representation has been used widely in our previous works, such as GeneFuse [24]. A progressive method for k-mer calculation is applied to accelerate k-mer generation.…”
Section: K-mer Generation and Representationmentioning
confidence: 99%
“…However, several studies have reported opposite data regarding the protumor effect of the microenvironment in BC. In particular, carcinoma-associated fibroblasts (CAFs), MSCs, TAMs, Breg, Treg, and Th2 lymphocytes may contribute to the development of metastases 3941. Litviakov et al reported the lack of clinical response to neoadjuvant anthracycline therapy in BC patients that was associated with the presence of M2 macrophages (YKL-39 – CCL18 + or YKL-39 + CCL18 – ) in the tumor 42…”
Section: Nact Modulates Immune Responses In the Tumor Microenvironmentmentioning
confidence: 99%